Comparison of Seventh and Eighth Editions of TNM_x000D_ Staging Classification and Evaluation of Survivals in_x000D_ Operated Non-Small Cell Lung Carcinomas:_x000D_ Single Center Experience - KOCAKAYA, DERYA; YUMUK, PERRAN FULDEN (My University, 2020)
Objectives: In this study, our purpose was to compare the survivals of the 7th and 8th editions of TNM staging system innon-small cell lung cancer (NSCLC).Methods: We retrospectively compared pathological staging and survival of 209 patients who were operated with thediagnosis of NSCLC between 2006 and 2017. In this study, we did not include metastatic patients, patients receivingpreoperative treatment, patients with low grade malignancy and patients with neuroendocrine carcinoma.Results: Three of the 31 stage 1A changed to 1A1, 11 to 1A2, 17 to 1A3; 16 of the 40 stage 1B changed to 2A; 2 of the38 stage 2B changed to 1B, 21 changed to 3A; 2 of the 41 stage 3A changed to 2B, 7 changed to 3B. When we groupedstages as I, II, III; there was a significant difference in prognostic effects between 7th edition stages (p=0.01) and 8thedition stages (p=0.02). Presence of surgical margin positivity, lymphatic, perineural and vascular invasion were poorprognostic factors (p<0.05).Conclusion: In our study, we observed similar survival rates according to the 7th and 8th editions of TNM staging systemwhich is used in the pathological staging of lung cancers.